EFEKTIVITAS MIKORISA ENDO BERBAGAI JENIS TANAH TERHADAP KETAHANAN SEMAI JATI (Tectona grandis L.f) AKIBAT JAMUR Fusarium sp. - HARYUNI HARYUNI; TEGUH SUPRIYADI (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2008)
The object of the researc was to obtaib get the nature of physicial chemistry various soil type (Entisol, Andisol, Vertisol, Alfisol), developing of microorganism in soil ground as operation involve without residu and effectivity inoculum Endomycorrhyza to plant teak core effect by Fusarium sp.This rearch was a lLaboratory plant Protection (Fitopathology ) and the , Soil Science, Glas House and Garden of Faculty of UTP Surakarta and Laboratory of teak center (Cepu, Jateng, it was done from April until December 2007...